Acoustic emission and specific film thickness (lambda) for spur gears - Raja Hamzah, Raja Ishak (British Inst Non-Destructive Testing, 2008)
This technical note presents experimental evidence of the correlation between AE activity and the specific film thickness (A) for operational spur gears. The film thickness was varied during operation by spraying liquid nitrogen on to the rotating gear wheel. Observations showed that at a lambda (A) value of 6.75 for both 700 and 1450 r/min, a significant drop in AE activity was noted. It is concluded that the evidence suggests that AE levels may offer an opportunity to quantify the level of asperity contact for meshing gears under a range of operating conditions; this is a significant finding in the development of the acoustic emission technology.